Qualitative study to support the content validity of the immune thrombocytopenia (ITP) Life Quality Index (ILQI). (15th July 2021) - Cooper, Nichola; Cuker, Adam; Bonner, Nicola; Ghanima, Waleed; Provan, Drew; Morgan, Mervyn; Taylor, Barbara; D'Alessio, Denise; Arnold, Donald; Viana, Ricardo
Summary: Immune thrombocytopenia (ITP) is an acquired immune‐mediated disorder. Bleeding is the primary symptom that presents in varying severities. ITP has a negative impact on health‐related quality of life (HRQoL). The ITP Life Quality Index (ILQI) was developed as a 10‐item patient‐reported outcome measure to assess impact on HRQoL in ITP. The objective of the present study was to confirm the content validity of the ILQI with a qualitative interview study in the UK involving 15 adult participants with ITP. Combined concept elicitation (CE) and cognitive debriefing (CD) interviews were conducted to explore the symptoms and impacts associated with ITP and confirm content validity of the draft ILQI. The CE phase elicited 14 ITP symptom concepts, including: bruising (all 15 patients, 100%), fatigue (14, 93·3%) and bleeding gums/blood blisters (13, 86·7%). Impacts included decreased ability to participate in sport (all 15 patients, 100%) and anxiety (12, 80%). The CD phase resulted in an adjustment to the ILQI recall period from 1 week to 'the past month'. Updates were made to improve relevance and response options. The qualitative interviews support the content validity of the ILQI and confirm that the concepts assessed are relevant and consistently understood and interpreted by adult patients with ITP.